Sacrificial Pets and Maternal Instinct in Gloria Sawai's "Mother's Day" and Barbara Gowdy's Falling Angels - Gordon, Neta (Atlantis, 2008)
Sawai's and Gowdy's representations of the deaths of kittens demonstrate how the category of pet depends on an inherent relationality to humans, thus confronting the extent to which hierarchical social coding has been normalized. Further, human-pet relations symbolically illuminate how motherhood is implicated in similar social codes that require self-sacrifice.